Cement augmentation of an angular stable plate osteosynthesis for supracondylar femoral fractures - biomechanical investigation of a new fixation device - Bäumlein, Martin (BMC Musculoskelet Disord, 2020)
BACKGROUND: Implant anchorage in highly osteoporotic bone is challenging, since it often leads to osteosynthesis failure in geriatric patients with supracondylar femoral fractures. Cementation of screws is presumed to prevent such osteosynthesis failure. This study aimed to investigate the effect of a newly designed, cementable fenestrated condylar screw for plate fixation in a biomechanical setting. METHODS: Eight pairs of osteoporotic cadaver femora with an average age of 77 years, ranging between 62 and 88 years, were randomly assigned to either an augmented or a non-augmented group. In both groups an instable 33-A3 fracture according to the AO / OTA classification was fixed with an angular stable locking plate. All right samples received a cement augmentation of their fenestrated condylar screws with calcium phosphate bone cement (CPC). Mechanical testing was performed at a load to failure mode by cyclic axial loading, using a servohydraulic testing machine. RESULTS: With a mean of 2475 N (95% CI: 1727–3223 N), the pressure forces resulting in osteosynthesis failure were significantly higher in specimen with cemented condylar screws as compared to non-cemented samples (1875 N (95% CI: 1320–2430 N)) (p = 0.024). In both groups the deformation of the constructs, with the distal screws cutting through the condylar bone, were the most frequent cause for failure. Analysis of axial stiffness (p = 0.889) and irreversible deformity of the specimens revealed no differences between the both groups (p = 0.161). No cement leakage through the joint line or the medial cortex was observed. CONCLUSION: Based on the present study results, the newly introduced, cementable condylar screw could be an encouraging feature for the fixation of supracondylar femoral fractures in patients with reduced bone quality in terms of load to failure accuracy of the cement application.